Emotions, management discourse and resistance: The revealing role of workplace bullying - Agnès Vandevelde-Rougale; Actualmente es investigadora asociada a Laboratorio del cambio social y político de la Universidad París Diderot (Francia). Correo:; Patricia Guerrero Morales; Pontificia Universidad Católica de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
This article questions emotions and managerial discourse as a means of resistance for victims of workplace harassment, that is, as a means of preservation and subjectivation. It is based on two case studies in the university sector, conducted in two different countries: Chile and Ireland. A socio-clinical approach is adopted, which articulates psychoanalytic and social theoretical perspectives and builds on the qualitative and critical paradigm. It is shown that emotions can help subjects gain awareness of the insidious violence of managerial discourse, and that the gap between different language practices can help create a space of freedom where the subject chooses his/her role and text, thus securing a margin for thought and action. But this article also shows that this resistance can have a high psychic and social cost. In conclusion, this text calls for the development of specific time and places to reflect on violence in the workplace, which cannot necessarily be organised by human resources departments.